Antecedents and Consequents of Multiculturalism and Social Diversity among Law Enforcement Workplace in Metro Manila - Gabon, Melina G. (Future Science / FSH-PH Publications, 2021)
This study describes the antecedents and consequents of multiculturalism and social diversity, and the perceptions of law enforcement personnel towards the consequents of multiculturalism and social diversity in the law enforcement workplace. This quantitative descriptive research determined the perceptions of 100 law enforcement personnel from the purposively selected law enforcement workplaces in Metro Manila. Data were analyzed using frequency and percentage distribution, mean and rank. The majority of the respondents recognized the utmost importance of multiculturalism and social diversity in a Law Enforcement workplace. Managing diversity in the law enforcement workplace means creating conditions that maximize the potential of its personnel to enhance organizational performance; and Multiculturalism promotes the integration of different cultures and the sharing of one's ideas and perspectives that lead to innovations have the highest mean scores of 3.75, respectively. On the other hand, Inclusive organizations can screen out highly prejudiced individuals and will find it easy to manage diverse employees with a mean score of 2.69. It can be gleaned that the majority of the respondents perceived that employing a culturally diverse law enforcement workforce has positive consequences to its people, workplace culture, and organizational climate. Therefore, law enforcement officers should support heterogeneous workplace advocacies, and that policymakers should reinvigorate the rigor of existing policies to sustain multicultural and social diversity in the entire organization.